Peran Masjid Gemma Prenduan Dalam Meningkatkan Kualitas Pendidikan Agama Islam Di Masyarakat - Nawalah, Khairatun Nawalah; Afifah, Muru’atul (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2025)
important place for Muslims, because the main function of the mosque is as a place of worship. The purpose of this study is to explore the mosque as an educational institution and the supporting and inhibiting factors in education at the Gemma mosque. This study uses a descriptive qualitative approach, with a case study type. Data were collected through interviews, observations, and documentation. While data analysis was carried out with a cycle of data collection, data reduction, data presentation and drawing conclusions. In testing the validity of the data, source triangulation and data triangulation were carried out. While the subjects of the study were the takmir administrators, congregation, and all matters related to the Gemma Prenduan mosque section. Based on the results of the study, it can be concluded that the role of the Gemma Prenduan mosque has been running smoothly and well. This can be seen from various Islamic education activities that have been held, such as the Majelis Taklim, namely various scientific studies and the existence of TPA, yellow book studies and the excitement of the month of Ramadan. So that it is able to create people with Islamic morals, faith, and piety. Supporting factors: the availability of mosques as a fairly good educational facility equipped with supporting educational facilities and infrastructure, the arrangement of a fairly good activity program so that the desired goals will be achieved, the number of congregations is large and always active. Inhibiting factors: human resources, lack of awareness of participants to follow longer activities, and time in following the activity process.